Peluang dan Aspek Hukum Investasi Asing dalam Bisnis Carbon Capture Storage di Indonesia - Marliana, Gina (LPPM Institut Pendidikan Nusantara Global, 2025)
Indonesia strengthens its commitment to Net Zero Emissions (NZE) through the ratification of the Paris Agreement (Law No. 16 of 2016) and establishes a regulatory framework for Carbon Capture and Storage (CCS) through Presidential Regulation No. 14 of 2024 and Minister of Energy and Mineral Resources Regulation No. 16 of 2024. These regulations aim to reduce emissions while attracting foreign direct investment (FDI). With its vast geographic potential, Indonesia is considered strategically positioned to become a carbon storage hub, and the existence of CCS regulations is expected to attract global investors. However, certainty for foreign investors cannot rely solely on CCS regulations; it must align with Law No. 25 of 2007 on Investment, which has been adjusted by the Job Creation Law (Law No. 6 of 2023) to ensure legal certainty and non-discrimination amid global competition. This paper assesses the alignment of the CCS legal framework with investment law provisions, identifies implementation gaps, and evaluates the application of non-discrimination principles. The research method employs normative/doctrinal legal research (statute and conceptual approach) based on regulations and literature, with qualitative analysis to formulate recommendations for strengthening the CCS investment climate.